THE IMPLEMENTATION OF COMMUNICATIVE LANGUAGE GAMES TO IMPROVE STUDENTS SPEAKING SKILL - Mairesa, Anindya Putri; Usman, Sriati; Wahyudin, Wahyudin; Mukrim, Mukrim (Tadulako University, 2023)
This research aimed to find out whether the Implementation of Communicative Language Games to Improve Speaking Skills of the eleventh-grade students of SMA Labschool Palu is effective in improving speaking skills of SMA Labschool Palu students. The design of this study was quasi-experimental which included students and class XI MIA 3 as an Experimental Group with a total of 20 students and XI IIS as a Control Group with a total of 20 students. The mean score of the pre-test of the experimental group is 41 while the control group is 45. The mean score of the post-test of the experimental group is 54 while the control group is 48. By using the 0.05 level of significance, the researchers computed the data and found that the value of the t-counted (2.702) is higher than the t-table (1.991.6). It means that the hypothesis is accepted. In other words, using the Communicative Language Games Technique can improve the students' speaking in the eleventh grade of SMA Labschool Palu.